PENGEMBANGAN HILIRISASI LIMBAH KELAPA DALAM MEWUJUDKAN DESA MANDIRI EKONOMI MELALUI BIKSAPA (BRIKET SERABUT KELAPA) - Fahreza, Rafi Achmad; Oktavianti, Anggun; Nurlaili, Hidayatul Alim; Syuhada, Yahya Ayyasy; Sa’adah, Naulus; Rahman, Muhamad Habil; Hidayatullah, Ahmad Syarif; Zahro, Indah Fatimatus; Dewi, Shopiana; Faradilla, Rizka; Prasetyawan, Safa Anindya Kaenori (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2024)
The community service program in Wates Kulon Village, Lumajang Regency, focuses on the utilizationof coconut waste, particularly coconut husks and shells, to produce briquettes as an alternative solid fuel.Coconut waste in the village has been underutilized, leading to lost economic opportunities. The program'sobjectives were to enhance local economic independence by converting coconut waste into high-valuebriquettes and to improve villagers' skills through training and outreach. The activities includedidentifying the village's potential, training on briquette production, and developing effective marketingstrategies, resulting in a profitable and sustainable business model. The findings show that the briquettesproduced have high calorific value and are competitive in the market, with a profit margin of Rp5,553.00per kilogram. The training sessions empowered 43 participants with new technical skills and marketingknowledge, enabling them to generate additional income. The program also received positive feedbackfrom local government officials, aligning with the village's mission to enhance economic welfare throughsustainable resource utilization. Overall, the program successfully contributed to the village's economicindependence by transforming coconut waste into a valuable product, supporting the broader goals ofsustainable development and poverty reduction.